2020
DOI: 10.1128/mmbr.00065-19
|View full text |Cite
|
Sign up to set email alerts
|

The Francisella tularensis Polysaccharides: What Is the Real Capsule?

Abstract: SUMMARY Francisella tularensis is a tier 1 select agent responsible for tularemia in humans and a wide variety of animal species. Extensive research into understanding the virulence factors of the bacterium has been ongoing to develop an efficacious vaccine. At least two such virulence factors are described as capsules of F. tularensis: the O-antigen capsule and the capsule-like complex (CLC). These two separate entities aid in avoiding host immune defenses but have not been clearly differentiated. These compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…However, some bacterial capsules are atypical: the capsule of Yersinia pestis is a protein polymer composed of 17-kDa subunits 11 , 12 , and the capsule of Bacillus anthracis consists of D-glutamic acid 13 . Additionally, the O-antigen capsule and the capsule-like complex (CLC) are identified as capsules of Francisella tularensis ( F. tularensis ) 14 . The O-antigen capsule is composed of mannose, rhamnose, and dideoxy sugars, whereas the CLC comprises proteins and carbohydrates 15 .…”
Section: Capsules Biosynthesismentioning
confidence: 99%
“…However, some bacterial capsules are atypical: the capsule of Yersinia pestis is a protein polymer composed of 17-kDa subunits 11 , 12 , and the capsule of Bacillus anthracis consists of D-glutamic acid 13 . Additionally, the O-antigen capsule and the capsule-like complex (CLC) are identified as capsules of Francisella tularensis ( F. tularensis ) 14 . The O-antigen capsule is composed of mannose, rhamnose, and dideoxy sugars, whereas the CLC comprises proteins and carbohydrates 15 .…”
Section: Capsules Biosynthesismentioning
confidence: 99%
“…Surface components of bacteria may serve as PAMPs through recognition by TLRs (Toll-like receptors). Certain pathogens, for example Francisella tularensis mask their surfaces (to evade immune sensing) by synthesizing a carbohydrate-based capsule that inhibits the antibody and complement deposition on the cell wall, and provide protection against microbicidal host responses (for instance, opsonization) ( 111 ). Some bacteria, for example, B. burgdorferi and Anaplasma use host lipids (as a building block for the biogenesis of their membranes) that helps in bypassing host immune responses by avoiding the immune cells ( 108 , 112 ).…”
Section: Arthropod Vectors Viruses and Innate Immune Responsesmentioning
confidence: 99%
“…In later studies, also Wilson et al (2011) have demonstrated that the expression of Vi antigen reduces C3b opsonization to the bacterial cell surface. In recent years, more and more attention has been paid to group IV polysaccharide capsules, which have a high degree of similarity in structure with the O-antigen of the LPS molecule (Caboni et al, 2015;Freudenberger Catanzaro and Inzana, 2020;Marshall and Gunn, 2015;Patrick et al, 2009). It has been shown that in Salmonella the O-antigen capsules are important in the processes of adhesion and in the persistence of bacteria in the environment (Barak et al, 2007;Crawford et al, 2008).…”
Section: Serum Resistance In the Context Of O-antigen Lengthmentioning
confidence: 99%